The Interconnected Network, a proposition - Paola Zellner Bassett (Veredes, Arquitectura y Divulgación, 2024)
As the International Archive of Women in Architecture (IAWA) completes its fourth decade in operation it pauses to reflect on its original goals within the context from which it emerged, as one initiative amongst many, in the quest to preserve the legacy of women in architecture. The IAWA seeks not only to better understand its role in the present context but also to reimagine its contribution to an equitable future, presenting here a proposition.